2009
DOI: 10.1111/j.1365-2648.2009.04992.x
|View full text |Cite
|
Sign up to set email alerts
|

A caring relationship with people who have cancer

Abstract: Closeness is an important foundation for caring, and acquires a special dimension in the care of people with cancer and their relatives. It derives from the personal and professional experiences of nurses in their own life stories. Nursing education should include a reflective approach in order to develop caring skills in oncology nursing that are not merely attuned to medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
1
20
0
3
Order By: Relevance
“…Being involved in close relationships may be challenging as well as mutually beneficial, and requires that nurses are present, listen actively, and are compassionate (Iranmanesh et al, 2009). Nurses in our study described that it was a privilege to be let in and involved in the patient's life, and, as Iranmanesh et al (2009) describe, it also provided a new insight into the nurses' own lives. It was also a privilege to have access to so many life stories, which, according to Taylor (1997), provides entrees into patients' life histories.…”
Section: Discussionmentioning
confidence: 65%
“…Being involved in close relationships may be challenging as well as mutually beneficial, and requires that nurses are present, listen actively, and are compassionate (Iranmanesh et al, 2009). Nurses in our study described that it was a privilege to be let in and involved in the patient's life, and, as Iranmanesh et al (2009) describe, it also provided a new insight into the nurses' own lives. It was also a privilege to have access to so many life stories, which, according to Taylor (1997), provides entrees into patients' life histories.…”
Section: Discussionmentioning
confidence: 65%
“…Para ello, es necesario que integren aspectos psicológicos y espirituales en su cuidado, con el apoyo de su equipo (16,27). Sin embargo, Wenzel sostiene que no siempre están las condiciones de apoyo suficientes, y que en algunas oportunidades se sienten solas (21).…”
Section: Discussionunclassified
“…Another study conducted in Iran showed that establishing a close care relationship with the cancer patient and his relatives is the basis of care. A reflective approach should be adopted in training oncology department nurses so as to help them develop their nursing care skills [17]. According to a study conducted in Iran, cancer patients are unable to live the way they used to live before the incidence of cancer, which is partly due to family, social and emotional problems among the many other problems they face and which reduce their quality of life.…”
Section: Research-based Evidence As Assumptions In Palliative Care Trmentioning
confidence: 99%
“…The results of some studies have shown that the implementation of an educational program can generate a positive attitude in nursing students as future nurses. Researchers emphasize the importance of adding palliative care training to nursing curricula in Iran as a means of improving the quality of end-of-life care [17].…”
Section: Research-based Evidence As Assumptions In Palliative Care Trmentioning
confidence: 99%
See 1 more Smart Citation